Modern Approaches to the Assessment of Productive Qualities of Sheep of Ascania Fine-Wool Breed - Olena Karatieieva; Vadim Posukhin (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis)
The study reflects the results of the evaluation analysis of the productive qualities of sheep of the Askanian fine-wool breed using modern methods. One of the main points in the selection and breeding business is the selection of animals with the best indicators of valuable economically useful traits. In modern practice, the selection of animals is carried out according to a complex of valuable traits and qualities, since the selection of animals for only one trait is not of particular value to the breeder. Using a number of modern techniques, which is one of the most relevant in this case. Calculations of the entropy-information analysis of live weight and wool length showed that the young stock of the Askanian fine-wool breed, in terms of the level of organization of systems, was characterized by ambiguous data on the organization of the system and relative entropy, which indicates sufficient disorganization of the system and provides opportunities for selection, has the potential to increase productivity. At the same time, sexual demorphism in the manifestation of signs of entropy was revealed, so the ewes of all experimental groups tended to reduce the level of unconditional entpropy. And the use of genetic and mathematical modeling showed a clear advantage in live weight of ewes and rams, which were the descendants of the first sire No. 483, which can characterize him as a carrier of the best hereditary characteristics regarding the ability to transmit high productive traits to the next generations.